2021
DOI: 10.3390/brainsci11040493
|View full text |Cite
|
Sign up to set email alerts
|

The Body across the Lifespan: On the Relation between Interoceptive Sensibility and High-Order Body Representations

Abstract: Background: Interoceptive information plays a pivotal role in building higher-order cognitive body representations (BR) that neuropsychological and neuroimaging evidence classifies as action-oriented (i.e., body schema) or non-action-oriented (i.e., visuo-spatial body map). This study aimed to explore the development of BR, considering the association with the interoceptive sensibility throughout the lifespan. Methods: Two hundred thirty-nine healthy participants divided into five age groups (7 to 8 years; 9 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Two hundred and thirty-eight healthy individuals participated in this study. They were grouped according to adulthood stage [ 28 , 37 , 38 ] into five age bands: the group of young adults consisted of 50 participants aged from 18 to 40 years old; the group of youngest-middle adults consisted of 50 participants aged from 41 to 50 years old; the group of middle adults consisted of 50 participants aged from 51 to 60 years old; the group of youngest-old adults consisted of 50 participants aged from 61 to 70 years old; and the group of middle-old adults consisted of 38 participants aged from 71 to 80 years old. Each age group was composed of 50 participants including 25 females and 25 males, but the middle-old adult group was composed of 18 females and 20 males.…”
Section: Methodsmentioning
confidence: 99%
“…Two hundred and thirty-eight healthy individuals participated in this study. They were grouped according to adulthood stage [ 28 , 37 , 38 ] into five age bands: the group of young adults consisted of 50 participants aged from 18 to 40 years old; the group of youngest-middle adults consisted of 50 participants aged from 41 to 50 years old; the group of middle adults consisted of 50 participants aged from 51 to 60 years old; the group of youngest-old adults consisted of 50 participants aged from 61 to 70 years old; and the group of middle-old adults consisted of 38 participants aged from 71 to 80 years old. Each age group was composed of 50 participants including 25 females and 25 males, but the middle-old adult group was composed of 18 females and 20 males.…”
Section: Methodsmentioning
confidence: 99%
“…However, the interactions between body image and interoception are complex as both concepts are multidimensional ( Khalsa et al, 2018 ; Prnjak et al, 2022 ) and are independently influenced by individual differences, especially age e.g., body image: ( Tiggemann, 2004 ; Karazsia et al, 2017 ; Hockey et al, 2021 ; Lacroix et al, 2023 ), interoception: ( Murphy et al, 2018 ; Raimo et al, 2021 ). As such, it is unclear how both body image and interoception interact with the body schema within the context of influential sociodemographic characteristics such as age.…”
Section: Introductionmentioning
confidence: 99%
“…Interoception also means one’s sense of the physiological condition of the body, and provides a basis for subjective feelings and emotions ( Craig, 2003 ). Many studies have suggested that individuals having a stronger interoceptive ability report more intense emotions ( Murphy et al, 2019 ), place more emphasis on the dimension of arousal in reporting their emotional experience ( Barrett and Simmons, 2015 ), and manifest a stronger link between their bodily reactions to emotional stimuli and their subjective arousal ratings ( Raimo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%